1995
DOI: 10.1016/0304-3959(94)00134-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic analgesia reduces R-III nociceptive reflex: further evidence concerning the multifactorial nature of hypnotic analgesia

Abstract: Mechanisms of hypnotic analgesia were investigated by examining changes in the R-III, a nociceptive spinal reflex, during hypnotic reduction of pain sensation and unpleasantness. The R-III was measured in 15 healthy volunteers who gave VAS-sensory and VAS-affective ratings of an electrical stimulus during conditions of resting wakefulness, suggestions for hypnotic analgesia, and attempted suppression of the reflex during non-hypnotic conditions. The H-reflex was also measured to monitor and control for general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
2
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(98 citation statements)
references
References 40 publications
10
83
2
3
Order By: Relevance
“…Third, a statistically significant decrease in pain ratings was observed during the HS only, a finding that is in agreement with our clinical practice. 2,15 Furthermore, our subjects testified that they were in the HS before each scan and confirmed their hypnotic experience during debriefing. Each of these points, taken in isolation, does not prove the presence of the HS in our subjects, but together they form a body of arguments that, by their cooccurrence, strongly suggest that this was indeed the case.…”
Section: Authenticity Of Hsmentioning
confidence: 69%
“…Third, a statistically significant decrease in pain ratings was observed during the HS only, a finding that is in agreement with our clinical practice. 2,15 Furthermore, our subjects testified that they were in the HS before each scan and confirmed their hypnotic experience during debriefing. Each of these points, taken in isolation, does not prove the presence of the HS in our subjects, but together they form a body of arguments that, by their cooccurrence, strongly suggest that this was indeed the case.…”
Section: Authenticity Of Hsmentioning
confidence: 69%
“…The NFR is a polysynaptic spinal reflex subserving withdrawal from potentially noxious stimuli. Individual differences in the intensity of electrocutaneous sural nerve stimulation required to elicit the NFR provide indirect evidence of supraspinal modulation, with higher thresholds suggesting enhanced descending inhibition and lower thresholds suggesting decreased inhibition of spinal nociceptive transmission (Willer et al, 1979;Kiernan et al, 1995;Danziger et al, 1998). For example, Willer et al (1979) reported that NFR was dampened during performance of a mental arithmetic task, and enhanced during anticipation of an intense noxious stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Willer et al (1979) reported that NFR was dampened during performance of a mental arithmetic task, and enhanced during anticipation of an intense noxious stimulus. More recent studies have examined the effects of hypnosis on NFR (Kiernan et al, 1995;Danziger et al, 1998), and have demonstrated that hypnotic suggestion of analgesia results in strong NFR inhibition in some participants while others show reflex facilitation. Animal studies provide convincing evidence of supraspinal modulation of nociceptive flexion reflexes, with the periaqueductal gray playing a major role in the control of spinal nociceptive neurons through relays in the rostral ventromedial medulla (Willis, 1988;Fields and Basbaum, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have concluded that hypnosis can impact pain by affecting a number of different neurophysiological processes that make up the pain matrix, rather than by influencing a single mechanism or process. Specifically, research indicates that hypnosis can impact activity in: (1) the periphery and spinal cord [67][68][69], (2) the thalamus [65,70,71], (3) the sensory cortices [72,73], (4) the insula [70,71,73], (5) the ACC [35,70,71,[73][74][75], and (6) the prefrontal cortex [70,71,73,76]. Given the extensiveness of these previous reviews, this section will briefly review past research that has examined the neurophysiological effects of hypnotic analgesia, specifically focused on the role of suggestion type [35,72,77].…”
Section: Neurophysiological Effects Of Hypnosismentioning
confidence: 99%